2015
DOI: 10.1017/s0021859615000040
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofGlomus aggregatumon photosynthetic function of snap bean in response to elevated ozone

Abstract: Snap bean genotypes (Phaseolus vulgaris L.) with different ozone (O 3 ) sensitivities (line S156: O 3 -sensitive; line R123: O 3 -tolerant) were grown for 70 days with or without inoculation of arbuscular mycorrhizal (AM) fungi under ambient (C AMB = 20 nanolitres (nl)/l and elevated (C MID = '50 nl/l and C HIG = 80 nl/l) O 3 . Sequential determinations (leaf injury, pigment concentration, chlorophyll fluorescence, photosynthesis, etc) were carried out during plant growth to evaluate mycorrhizal influence on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
2
3
0
Order By: Relevance
“…The mean O 3 concentrations at the three sampling sites were in the order of 130 mg/m 3 (MLP) o 145 mg/m 3 (YGZ) o147 mg/m 3 (BZF), which was negatively related with the mean leaf TCH. It was reported that O 3 would reduce the effect of photosynthetic function in plants (Wang et al, 2015), and stomatal movements regulate gas exchange; which directly affect the efficiency of photosynthesis and the sensitivity of plants to air pollutants such as ozone (Nagatoshi et al, 2016). Our results indicate that the TCH value in plant leaves decreased with higher concentration of SO 2 and O 3 , which is in agreement with previous studies Wei et al, 2014 ).…”
Section: Total Chlorophyll Content (Tch)supporting
confidence: 92%
“…The mean O 3 concentrations at the three sampling sites were in the order of 130 mg/m 3 (MLP) o 145 mg/m 3 (YGZ) o147 mg/m 3 (BZF), which was negatively related with the mean leaf TCH. It was reported that O 3 would reduce the effect of photosynthetic function in plants (Wang et al, 2015), and stomatal movements regulate gas exchange; which directly affect the efficiency of photosynthesis and the sensitivity of plants to air pollutants such as ozone (Nagatoshi et al, 2016). Our results indicate that the TCH value in plant leaves decreased with higher concentration of SO 2 and O 3 , which is in agreement with previous studies Wei et al, 2014 ).…”
Section: Total Chlorophyll Content (Tch)supporting
confidence: 92%
“…In this study, plants sprayed with distilled water had higher F o and lower F v /F m under 2 × ambient O 3 compared with ambient air, which indicated that photoinhibition and photoinactivation of photosystem II complexes occurred (Bradbury and Baker, 1986;Leipner et al, 2001;Thwe et al, 2014). This result is in accordance with other studies of O 3 effects on snap bean (Flowers et al, 2007;Wang et al, 2015). The stable F o and F v /F m in plants sprayed with EDU or KIN between different O 3 concentrations suggested that the EDU or KIN spraying protected photosystem II complexes and avoided the occurrence of photoinhibition.…”
supporting
confidence: 91%
“…This symbiont combination also led to increased gas exchange relative to non-AM plants with exposure to low temperature stress ( Zhu et al, 2010 ). AM symbiosis has also helped bolster CER, g s , and E with exposure to ozone stress, in Phaseolus vulgaris colonized by Glomus aggregatum ( Wang et al, 2015 ). AM symbiosis has resulted in higher gas exchange rates when plants were faced with heavy metal stress, e.g., chromium by Helianthus annuum colonized by G. intraradices ( Davies et al, 2002 ) and Ampelopteris prolifera colonized by Glomus deserticola ( Singh et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%